Comparison of protective efficacy between two DNA vaccines encoding DnaK and GroEL against fish nocardiosis. Issue 95 (December 2019) - Chen, Jianlin; Wang, Wenji; Hou, Suying; Fu, Weixuan; Cai, Jia; Xia, Liqun; Lu, Yishan
Abstract: Fish nocardiosis is a chronic granulomatous bacterial disease mainly caused by three pathogenic bacteria, including Nocardia seriolae, N . asteroids and N . salmonicida . Molecular chaperone DnaK and GroEL were identified to be the common antigens of the three pathogenic Nocardia species in our previous studies. To evaluate the immune protective effect of two DNA vaccines encoding DnaK or GroEL against fish nocardiosis, hybrid snakehead were vaccinated and the immune responses induced by these two vaccines were comparatively analyzed. The results suggested it needed at least 7 d to transport DnaK or GroEL gene from injected muscle to head kidney, spleen and liver and stimulate host's immune system for later protection after immunization by DNA vaccines. Additionally, non-specific immunity parameters (serum lysozyme (LYZ), peroxidase (POD), acid phosphatase (ACP), alkaline phosphatase (AKP) and superoxide dismutase (SOD) activities), specific antibody (IgM) production and immune-related genes ( MHCIα, MHCIIα, CD4, CD8α, IL-1β and TNFα ) were used to evaluate the immune responses induced in vaccinated hybrid snakehead. It proved that all the above-mentioned immune activities were significantly enhanced after immunization with these two DNA vaccines. The protective efficacy of pcDNA-DnaK and pcDNA-GroEL DNA vaccines, in terms of relative percentage survival (RPS), were 53.01% and 80.71% respectively. It demonstrated that these two DNA vaccines could increase the survival rate of hybrid snakehead against fish nocardiosis, albeit with variations in immunoprotective effects. Taken together, these results indicated that both pcDNA-DnaK and pcDNA-GroEL DNA vaccines could boost the innate, humoral and cellular immune response in hybrid snakehead and show highly protective efficacy against fish nocardiosis, suggesting that DnaK and GroEL were promising vaccine candidates. These findings will promote the development of DNA vaccines against fish nocardiosis in aquaculture. Graphical abstract: We identified the secreted proteins of DnaK and GroEL from extracellular products of Nocardia seriolae by shotgun mass spectrometry (MS) and they were used as antigens to develop DNA vaccines, respectively. Both pcDNA-DnaK and pcDNA-GroEL DNA vaccines could boost the innate, humoral and cellular immune response in hybrid snakehead and show highly protective efficacy against fish nocardiosis, suggesting that DnaK and GroEL were promising vaccine candidates. Image 1 Highlights: DnaK and GroEL were identified as secreted proteins of  N .  seriolae . Two DNA vaccines were prepared by applying DnaK and GroEL as antigen. Both pcDNA-DnaK and pcDNA-GroEL DNA vaccines could boost the innate, humoral and cellular immune response in hybrid snakehead and show highly protective efficacy against fish nocardiosis.